Application of Rotary Dryer Modification Technology to Increase Animal Feed Production Efficiency - Moondra Zubir; Agus Junaidi; Rini Selly; Siti Rahmah; Hafni Indriati Nasution; Zainuddin Muchtar (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2022)
Lorong Ujung Tanjung Dua, Lingk 15, Bagan Deli Village, Belawan, North Sumatra became the location of this community research and service with Mr. Deddy Suryono as the owner of the business as the partner. His business activity is processing seafood shell waste into animal feed products. This business partner had problems whereas manual drying prolong the time due to the natural causes. Furthermore, the market of the product was in lower level due to the absence of explanation of the content of the product and also the brand name. One of the solution to propose is a high quality functional drying oven with eligible size and fixed temperature. Secondly, to increase the marketing of the product it need to be standardize by laboratory and make the brand name. The results, Rotary Dryer Modification Technology was used as the dryer which increased the product 4 times in quantity. The product was analysed in laboratory with three type of products whereas Shrimp Skin, Crab Skin and Fish Skin. The lab result showed that fish skin has the highest protein more than 50%. The brand name then named as EBYPRO.